Exonuclease VII repairs quinolone-induced damage by resolving DNA gyrase cleavage complexes - Huang, Shar-yin N. (Sci Adv, 2021)
The widely used quinolone antibiotics act by trapping prokaryotic type IIA topoisomerases, resulting in irreversible topoisomerase cleavage complexes (TOPcc). Whereas the excision repair pathways of TOPcc in eukaryotes have been extensively studied, it is not known whether equivalent repair pathways for prokaryotic TOPcc exist. By combining genetic, biochemical, and molecular biology approaches, we demonstrate that exonuclease VII (ExoVII) excises quinolone-induced trapped DNA gyrase, an essential prokaryotic type IIA topoisomerase. We show that ExoVII repairs trapped type IIA TOPcc and that ExoVII displays tyrosyl nuclease activity for the tyrosyl-DNA linkage on the 5′-DNA overhangs corresponding to trapped type IIA TOPcc. ExoVII-deficient bacteria fail to remove trapped DNA gyrase, consistent with their hypersensitivity to quinolones. We also identify an ExoVII inhibitor that synergizes with the antimicrobial activity of quinolones, including in quinolone-resistant bacterial strains, further demonstrating the functional importance of ExoVII for the repair of type IIA TOPcc.